Efficacy and safety of cisplatin versus miriplatin in transcatheter arterial chemoembolization and transarterial infusion chemotherapy for hepatocellular carcinoma: A randomized controlled trial. Issue 5 (24th July 2014) - Otsuji, Kentarou; Takai, Koji; Nishigaki, Yoichi; Shimizu, Shougo; Hayashi, Hideki; Imai, Kenji; Suzuki, Yusuke; Hanai, Tatsunori; Ideta, Takayasu; Miyazaki, Tsuneyuki; Tomita, Eiichi; Shimizu, Masahito; et al.
Abstract : Aim: Transcatheter arterial chemoembolization (TACE) and transarterial infusion chemotherapy (TAI) are the main therapeutic strategies for treatment of advanced hepatocellular carcinoma (HCC). We conducted a randomized controlled trial to compare the efficacy and safety of cisplatin and miriplatin in TACE and TAI. Methods: Patients with HCC of indication for TACE or TAI were randomly assigned to receive either cisplatin or miriplatin (49 patients per group) between April 2010 and May 2013. The primary end‐point was the therapeutic effect (TE) 3 months after initial treatment, and the secondary end‐point was overall survival. Results: TE could be evaluated in 26 patients of the cisplatin group and 20 patients of the miriplatin group. In the cisplatin group, 11 (42.3%) and 15 (57.7%) patients were classified as showing TE3 + 4 and TE1 + 2, respectively, while in the miriplatin group, each number was nine (45.0%) and 11 (55.0%) ( P  = 0.8551). Furthermore, no significant difference in overall survival was found between two groups for all patients ( P  = 0.905) or those treated only with TAI (10 in the cisplatin group and eight in the miriplatin group; P  = 0.695). TE3 + 4 group showed better overall survival than TE1 + 2 group ( P  = 0.0263). Grade 4 or higher adverse event did not occur in either group. Creatinine levels in the cisplatin group rose 3 days after TACE or TAI ( P  = 0.0397). Conclusion: Cisplatin and miriplatin had equal efficacy for TACE and TAI, but cisplatin should be avoided for patients with renal dysfunction or inadequate hydration. Good TE improved overall survival.